2021
DOI: 10.1021/acs.analchem.1c00548
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cellular Uptake of Polymer Dots for Quantitative Imaging and Photodynamic Therapy

Abstract: There is a great deal of interest in the development of nanoparticles for biomedicine. The question of how many nanoparticles are taken up by cells is important for biomedical applications. Here, we describe a fluorescence method for the quantitative measurement of the cellular uptake of polymer dots (Pdots) and a further estimation of intracellular Pdots photosensitizer for fluorescence imaging and photodynamic therapy. The approach relies on the high brightness, excellent stability, minimal aggregation quenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
2
11
1
Order By: Relevance
“…These observations are attributed to the presence of non-emissive exciton quenching sites or recombination centers (Q). , The number, nature, and location of Q centers appear to be highly dependent on several parameters associated with CPN preparation conditions. For example, the fluorescence lifetime (τ 0 CPN ) and quantum yield (Φ F0 CPN ) of our F8BT CPNs in the absence of dyes are different from those reported by some authors but matches those reported by other authors. , The nature of Q sites has been associated with a number of entities such as polymer synthesis defects and charged species such as hole/electron–polarons. In particular, there are a significant number of publications describing efficient exciton quenching by charged species (polarons).…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…These observations are attributed to the presence of non-emissive exciton quenching sites or recombination centers (Q). , The number, nature, and location of Q centers appear to be highly dependent on several parameters associated with CPN preparation conditions. For example, the fluorescence lifetime (τ 0 CPN ) and quantum yield (Φ F0 CPN ) of our F8BT CPNs in the absence of dyes are different from those reported by some authors but matches those reported by other authors. , The nature of Q sites has been associated with a number of entities such as polymer synthesis defects and charged species such as hole/electron–polarons. In particular, there are a significant number of publications describing efficient exciton quenching by charged species (polarons).…”
Section: Resultscontrasting
confidence: 73%
“…For example, the fluorescence lifetime (τ 0 CPN ) and quantum yield (Φ F0 CPN ) of our F8BT CPNs in the absence of dyes are different from those reported by some authors 33−35 but matches those reported by other authors. 36,37 The nature of Q sites has been associated with a number of entities such as polymer synthesis defects and charged species such as hole/electron−polarons. In particular, there are a significant number of publications describing efficient exciton quenching by charged species (polarons).…”
Section: Resultsmentioning
confidence: 99%
“…Polyfluorene and its derivatives have attracted considerable attention in fluorescent imaging, 22 cellular labeling 23,24 as well as ECL sensing 25,26 because of the high fluorescence quantum yield, excellent photostability and non-toxic. 27,28 Two kinds of polymer dots were prepared using different polyfluorene derivatives to construct ECL biosensors for detecting Pb 2+ and proteins in the case of amine as coreactant, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, CPN biocompatibility in vitro and in vivo has been reported, which encouraged us to continue evaluating this type of nanomaterial for clinical use [ 19 , 21 , 22 ]. In accordance with the development of CPNs that specifically target cancer cells, thus reducing adverse side effects while improving therapeutic efficacy, different approaches have been considered to conjugate these types of nanoparticles to highly selective recognition molecules, such as antibodies or peptides, against cell-membrane receptors overexpressed on cancer cells [ 23 , 24 , 25 ]. The exquisite selectivity of oligonucleotide aptamers for cancer cell targeting and their ability to actively internalize into target cells via receptor-mediated endocytosis [ 26 ] make these biomolecules excellent candidates to improve the cancer cell labelling capacity and PDT efficacy.…”
Section: Introductionmentioning
confidence: 99%